EFEKTIVITAS PENGAWASAN PARTISIPATIF DALAM MENGURANGI JUMLAH PELANGGARAN PEMILU 2024 DI JAWA BARAT - Amal, Bakhrul (Bawaslu Provinsi Jawa Barat, 2024)
The 2019 General Election in Indonesia, particularly in West Java Province, recorded a high number of violations, with political money practices being the most dominant. Bawaslu West Java reported 942 violations during the 2019 Election, highlighting the need for stricter oversight in the 2024 Election. One approach that can be utilized is participatory oversight, which involves the public in monitoring and reporting electoral violations. The research problem in this study is to assess the effectiveness of participatory oversight in reducing election violations in West Java during the 2024 Election. This study uses a socio-legal method with a statute approach and a conceptual approach. The data used consists of primary data obtained from Bawaslu activity documentation and secondary data, including regulations, journals, and books related to electoral matters. The discussion in this study elaborates on the various initiatives carried out by Bawaslu West Java to enhance participatory oversight, such as educational programs for participatory monitors, community forums, oversight corners, collaboration with universities, and digital communities. The findings show that participatory oversight has successfully reduced the number of election violations in West Java, from 942 violations in the 2019 Election to 582 violations in the 2024 Election. In conclusion, participatory oversight has proven effective in reducing election violations in West Java. This study recommends that Bawaslu continue to expand and deepen participatory oversight by utilizing digital technology and strengthening electoral education across all layers of society.